Theology and Reflexivity - Pilario, Daniel Franklin (Louvain studies, 2018)
This article proposes a threefold reflexive program for theological method - on the level of personal social locations of theologians, on the level of their belonging to the theological field as distinct from other fields, and on the level of their membership to the academic field itself. Using categories from Pierre Bourdieu and some practical structural forms, the author argues that theology can be more reflexive, thus, more faithful to its role in the Church if it is always conscious that it does not have the last word in the interpretation of reality. The poor possesses this epistemological privilege; or, better still, the God who reveals himself in the life of the excluded and dispossessed. The author situates his discussion on reflexivity from the rough grounds' of a dumpsite parish where he regularly ministers on weekends and brings the reflection back to the present politically volatile situation in the Philippines.